The Skin Microbiome of Patients With Atopic Dermatitis Normalizes Gradually During Treatment - Khadka, Veda D.; Key, Felix M.; Romo-González, Carolina; Martínez-Gayosso, Adrián; Campos-Cabrera, Blanca L.; Gerónimo-Gallegos, Armando; Lynn, Tucker C.; Durán-McKinster, Carola; Coria-Jiménez, Rafael; Lieberman, Tami D.; García-Romero, Maria T. (Frontiers in Cellular and Infection Microbiology, 2021)
Background Atopic dermatitis (AD) is characterized by an altered skin microbiome dominantly colonized by S. aureus. Standard treatment includes emollients, anti-inflammatory medications and antiseptics. Objectives To characterize changes in the skin microbiome during treatment for AD. Methods The skin microbiomes of children with moderate-to-severe AD and healthy children were investigated in a longitudinal prospective study. Patients with AD were randomized to receive either standard treatment with emollients and topical corticosteroids or standard treatment with the addition of dilute bleach baths (DBB) and sampled at four visits over a three-month period. At each visit, severity of AD was measured, swabs were taken from four body sites and the composition of the microbiome at those sites was assessed using 16S rRNA amplification. Results We included 14 healthy controls and 28 patients. We found high relative abundances of S. aureus in patients, which correlated with AD severity and reduced apparent alpha diversity. As disease severity improved with treatment, the abundance of S. aureus decreased, gradually becoming more similar to the microbiomes of healthy controls. After treatment, patients who received DBB had a significantly lower abundance of S. aureus than those who received only standard treatment. Conclusions There are clear differences in the skin microbiome of healthy controls and AD patients that diminish with treatment. After three months, the addition of DBB to standard treatment had significantly decreased the S. aureus burden, supporting its use as a therapeutic option. Further study in double-blinded trials is needed.